Assessment of experimental infection for dogs using Gallus gallus chorioallantoic membranes inoculated with Neospora caninum - Munhoz, Alexandre Dias; Mineo, Tiago Wilson Patriarca; Alessi, Antonio Carlos [UNESP]; Lopes, Carlos Wilson Gomes; Machado, Rosangela Zacarias [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2013)
The aim of this study was to evaluate parasitism kinetics and tissue lesions in the first week of infection by Neospora caninum in dogs fed Gallus gallus chorioallantoic membranes (CMs) previously infected in ovo. Five two-month-old pups were used. Each dog was given five CMs that were previously infected with N. caninum via the oral route. Four animals were euthanized in the first week of infection. All four dogs had their stools examined one week prior to and up to the day they were euthanized. The stools of the uneuthanized dog were collected for 30 days. After euthanasia, organ sections were utilized for histopathology, immunohistochemistry, indirect immunofluorescent tissue reactions, PCR and real-time PCR to detect parasites. Necropsy revealed that the small and large intestines, spleen, and lungs were affected. No oocysts or N. caninum DNA were identified in the stool samples. Real-time PCR was the most sensitive technique used to detect the protozoa in tissues, which were identified in 41% of the analyzed samples. Our results indicate that an experimental model using previously infected CMs appears to be a useful model for the study of the host-parasite relationship during the infection's acute phase.

O objetivo deste estudo foi avaliar a cinética de parasitismo e lesões teciduais, na primeira semana de infecção por Neospora caninum, em cães alimentados com membranas corioalantóicas (MCs) de Gallus gallus, previamente infectadas in ovo. Foram utilizados cinco filhotes de dois meses de idade. Cada cão recebeu cinco MCs previamente infectadas com N. caninum, por via oral. Quatro animais foram eutanasiados na primeira semana de infecção. Todos os quatro cães tiveram suas fezes examinadas uma semana antes e até o dia em que foram eutanasiados. O cão que não foi eutanasiado teve suas fezes colhidas durante 30 dias. Depois da eutanasia fragmentos de órgãos foram processados para histopatologia, imuno-histoquímica, reação de imunofluorescência indireta em tecidos, PCR e PCR em tempo real para detecção do parasito. A necropsia revelou que os intestinos delgado e grosso, baço e pulmões foram os órgãos afectados. Oocistos de N. caninum não foram identificados nas amostras de fezes. A PCR em tempo real foi a técnica mais sensível para detectar o protozoário nos tecidos, sendo identificados em 41% das amostras analisadas. Os nossos resultados indicam que o modelo experimental utilizando MCs evidenciou ser um bom modelo para estudar a relação parasito-hospedeiro durante a fase aguda da infecção.
Avaliação da infecção experimental de cães com membranas córion-alantóides de Gallus gallus inoculadas com Neospora caninum
Keywords: Neosporosis; acute phase; infection; real-time PCR; immunohistochemistry; Neosporose; fase aguda; infecção; PCR em tempo real; imonu-histoquímica